A Novel UWB MIMO Antenna with High Isolation for Sub-6 GHz Band Application - et. al., Karthi J, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A compact Multiple input Multiple output (MIMO) patch antenna with Electromagnetic Band Gap (EBG) structure to provide high isolation and defected ground for sub-6 GHz UWB 5G application is presented. The proposed design comprises of two symmetrical radiating semi-circular patch antenna with stubs and slots separated by a slotted EBG structure with the size of 30 x 30 mm2. The performance of the antenna is also been studied under the topics of impedance bandwidth, radiation patterns, envelope correlation coefficient and gain. The proposed design resonates at 3.7GHz and 5.05GHz with a return loss of -40dB and -35dB respectively and has a bandwidth of 3GHz to 5.05GHz and ECC less than 0.007 throughout the band. The proposed antenna is designed and simulated using Computer Simulation Technology (CST)..